Assessment of a deep learning model for algal toxin forecasting in coastal Maine - Johnathan Evanilla; Nicholas R. Record; Benjamin Tupper; Bryant Lewis; David W. Miller; Kohl Kanwit; Craig Burnell; Stephen D. Archer (Harmful Algae, 2026)

Stock composition and movement patterns of striped bass in the Saco River Estuary, Maine, USA, using acoustic telemetry - Benjamin P. Gowell; Alexa Cacacie; Jessica B. Maguire; Ashley M. Nicoll; Mike G. Frisk; Keith J. Dunton; Craig Tennenhouse; Jason Doll; John A. Mohan; William Kochtitzky; Michelle Caputo (Estuarine, Coastal and Shelf Science, 2026)

Green competition at sea: Dynamic modeling of alternative fuel adoption and fleet competitiveness - Siti Marsila Mhd Ruslan; Teuku Naraski Zahari; Mohd Tarmizi Osman; Kasypi Mokhtar; Wan Nurdiyana Wan Mansor; Norjipin Saidi; Osman Turan; Benjamin Craig McLellan (Ocean & Coastal Management, 2026)

Efficacy of an Inactivated Bacterin Vaccine Against Emerging Streptococcus dysgalactiae in Channel Catfish ( Ictalurus punctatus ) - Brent M. Vuglar; Krishna P. Singha; Craig A. Shoemaker; Benjamin H. Beck; Taylor I. Heckman; Jason W. Abernathy; Julio C. García; Eric Peatman; Timothy J. Bruce (Journal of Fish Diseases, 2026)
Lancefield Group C Streptococcus dysgalactiae recently emerged as a catfish pathogen in the US. Reports from hatcheries suggest S. dysgalactiae causes substantial broodfish loss. We aimed to develop a challenge model and evaluate vaccine efficacy against S. dysgalactiae in juvenile channel catfish ( Ictalurus punctatus ). Three S. dysgalactiae (14–1, 14–24 and 14–25) isolates were tested for virulence. Intracoelomic (IC) injection demonstrated S. dysgalactiae 14–1 was the most virulent. Reisolated 14–1 was used to develop a formalin‐killed cell (FKC) vaccine. Catfish (200) were immunized via IC injection of 100 μL FKC with adjuvant (1:1 v/v), and another 200 catfish were sham vaccinated. Five fish from each group were bled for antibody titre every 14 days. At 28 and 56 days post‐vaccination (dpv), subsets of both groups were challenged with S. dysgalactiae via IC injection (200 μL/fish) in triplicate (20 fish/tank). Cumulative percent mortality was significantly ( p S. dysgalactiae bacterin induced humoral immunity and protected juvenile catfish. Future studies are planned to evaluate this bacterin in broodfish.

Advancing conservation through virtual livestock fencing - Drew E. Bennett; Travis Brammer; Jerod A. Merkle; Kurt T. Smith; Shawn Regan; Temple Stoellinger; Arthur Middleton; Kristin Barker; Jacob P. Hochard; Patrick E. Lendrum; Erin Welty; Craig Benjamin; et al. (Biological Conservation, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Chemical composition of post-fire epicormic foliage affects nutritional quality for folivores - Benjamin Wagner; Kara N. Youngentob; Karen J. Marsh; Anu Singh; Craig R. Nitschke (Forest Ecology and Management, 2026)

Efficacy of orally-delivered virulent Aeromonas hydrophila bacterin vaccines in channel catfish (Ictalurus punctatus) - Allison Wise; Benjamin H. Beck; Bradley M. Richardson; Troy J. Bader; Eric Peatman; Mark R. Liles; Priscilla C. Barger; Craig A. Shoemaker (Aquaculture, 2026)

Risk dynamics and strategies of China's solar PV industry chain under trade frictions: A review - Yujia Zhao; Benjamin Craig McLellan; Chaofan Wang; Jing Shuai; Wanting Xiang; Chuanmin Shuai (Energy Policy, 2026)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

Matching planting methods to species and site conditions is key in seed-based intertidal seagrass restoration - Lucy Coals; Benjamin L.H. Jones; Ally J. Evans; Richard K.F. Unsworth; Laney Callahan; Rhys A. Coleman; Laura L. Govers; Max L.E. Gräfnings; Emma L. Jackson; Craig D.H. Sherman (Marine Pollution Bulletin, 2025)

An Overview of Vaccine Development Strategies for Columnaris‐Causing Bacteria in Cultured Fish - Courtney E. Harrison; Benjamin R. LaFrentz; Craig A. Shoemaker; Miles D. Lange; Mark R. Liles; Haitham H. Mohammed; Benjamin H. Beck; Emily M. Churchman; Eric Peatman; Timothy J. Bruce (Journal of Fish Diseases, 2025)
Columnaris disease, caused by columnaris‐causing bacteria (CCB), affects cultured and wild freshwater fish worldwide. Belonging to the phylum Bacteroidota and the family Flavobacteriaceae, CCB are gram‐negative, yellow‐pigmented bacteria that are presumed ubiquitous in freshwater habitats. Since the first report of the disease in 1922, growth and survival, pathogenesis, and transmission of these pathogens have been intensely researched, aiding in a greater understanding of host‐pathogen interactions. Recent classification of Flavobacterium columnare into four distinct species based on genetic similarity, including F. columnare , F. covae , F. davisii , and F. oreochromis , along with their host associations is critical to understanding disease dynamics and prevention strategies. Outbreaks of the disease typically follow stressful events where CCB colonise external tissues, such as skin and gill. Vaccination against columnaris disease was practiced as early as the 1970's. Since then, many different vaccine types have been under development, including killed, live‐attenuated, recombinant, and micro‐ and nano‐particle vaccines. Among the different CCB vaccine types, immune responses and level of protection have been variable. However, some vaccines have been reported to offer moderate‐significant protection in some fish species. This review synthesises the current knowledge of CCB taxonomy, genetic diversity, virulence, and immunity in various aquaculture species, with the goal of identifying knowledge gaps to be addressed for future CCB vaccine development. The development of an efficacious columnaris vaccine remains a challenge, with promising results in the laboratory that have yet to be reflected under production settings. This highlights the need for improved strategies tailored to the species of CCB most appropriate for the target host species.

The effect of enhanced glycolysis on cardiac aging - Anna Faakye; Kylene M. Harold; Satoshi Matsuzaki; Atul Pranay; Maria F. Mendez Garcia; Brooke L. Loveland; Sandra N. Rigsby; Frederick F. Peelor; Craig Eyster; Benjamin F. Miller; Timothy M. Griffin; Michael Kinter; et al. (GeroScience, 2025)
Cardiac aging is associated with metabolic changes, including an increased reliance on glycolysis, and an increased susceptibility to cardiovascular diseases. This study explores the relationship between enhanced cardiac glycolysis and aging using the Glyco Hi mouse model, characterized by constitutively elevated glycolysis. We compared cardiac function, metabolism, mitochondrial performance, and hallmarks of aging between aged (21 and 24 months) Glyco Hi and wild-type (WT) mice across sexes. Our findings reveal modest reductions in cardiac function in aged Glyco Hi mice compared to WT mice, with sex-specific differences in heart size and collagen concentration. Female Glyco Hi hearts exhibited hypertrophy without fibrosis, while males showed elevated collagen levels. Whole-body metabolic assessments revealed similar energy expenditure and respiratory patterns across genotypes, with females displaying less circadian-associated variation in metabolism. Mitochondrial analyses showed that aged Glyco Hi hearts maintained metabolic adaptations favoring glycolysis but did not exhibit significant bioenergetic dysfunction or oxidative stress. Pyruvate dehydrogenase activity, initially elevated in younger Glyco Hi hearts, normalized to WT levels with age. Proteomic and metabolomic analyses highlighted distinct profiles between genotypes, with Glyco Hi hearts exhibiting increased glycolytic enzyme levels and reduced abundance of fatty acid oxidation proteins. Despite these differences, indicators of oxidative stress, proteostasis, and cellular senescence were comparable between genotypes, suggesting no acceleration of aging-related dysfunction. This study demonstrates that increased cardiac glycolysis alone does not suffice to drive accelerated cardiac aging. Instead, metabolic and functional changes in aged Glyco Hi hearts reflect adaptations rather than pathological declines, providing insights into potential metabolic targets for interventions against cardiac aging.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Forecasting deforestation and carbon loss across New Guinea using machine learning and cellular automata - Christoph Parsch; Benjamin Wagner; Jayden E. Engert; Rawati Panjaitan; William F. Laurance; Craig R. Nitschke; Holger Kreft (Science of The Total Environment, 2025)

Identification and epidemiological analysis of a putative novel hantavirus in Australian flying foxes - Craig S. Smith; Darren J. Underwood; Anita Gordon; Michael J. Pyne; Anna Smyth; Benjamin Genge; Luke Driver; David G. Mayer; Jane Oakey (Virus Genes, 2025)
In July 2017, an investigation into the cause of neurological signs in a black flying fox ( Pteropus alecto , family Pteropodidae ) identified a putative novel hantavirus (Robina virus, ROBV, order Bunyavirales , family Hantaviridae , genus Mobatvirus ) in its brain. Analysis of the evolutionary relationship between other hantaviruses using maximum-likelihood, a systematic Bayesian clustering approach, and a minimum spanning tree, all suggest that ROBV is most closely related to another Mobatvirus , Quezon virus, previously identified in the lung of a Philippine frugivorous bat ( Rousettus amplexicaudatus , also family Pteropodidae ). Subsequently, between March 2018 and October 2023, a total of 495 bats were opportunistically screened for ROBV with an experimental qRT-PCR. The total prevalence of ROBV RNA detected in Pteropus spp. was 4.2% (95% CI 2.8–6.4%). Binomial modelling identified that there was substantial evidence supporting an increase ( P = 0.033) in the detection of ROBV RNA in bats in 2019 and 2020 suggesting of a possible transient epidemic. There was also moderate evidence to support the effect of season ( P = 0.064), with peak detection in the cooler seasons, autumn, and winter, possibly driven by physiological and ecological factors similar to those already identified for other bat-borne viruses. This is Australia’s first reported putative hantavirus and its identification could expand the southern known range of hantaviruses in Australasia.

Microplastic biomonitoring studies in aquatic species: A review & quality assessment framework - Benjamin de Jourdan; Danielle Philibert; Davide Asnicar; Craig Warren Davis (Science of The Total Environment, 2024)

Stand structure and disturbance history of old-growth blue pine (Pinus wallichiana) forests in the Bhutan Himalaya - Karma Tenzin; Craig R. Nitschke; Kathryn J. Allen; Benjamin Wagner; Thiet V. Nguyen; Patrick J. Baker (Dendrochronologia, 2024)

Optimization berth allocation in container terminals: A Pyomo and Google Colab approach - Siti Nur 'Ain Nazri; Kasypi Mokhtar; Anuar Abu Bakar; Benjamin Craig Mclellan; Siti Marsila Mhd Ruslan (Ocean & Coastal Management, 2024)

Recent sedimentology at the grounding zone of the Kamb Ice stream, West Antarctica and implications for ice shelf extent - Theo Calkin; Gavin B. Dunbar; Cliff Atkins; Andrew Carter; Jason J. Coenen; Shaun Eaves; Catherine E. Ginnane; Nicholas R. Golledge; David M. Harwood; Huw J. Horgan; Benjamin C. Hurwitz; Christina Hulbe; et al. (Quaternary Science Reviews, 2024)

Assessment of dietary yeast‐based additives for cultured catfish and tilapia health - Guillaume Cacot; D. Allen Davis; Benjamin R. LaFrentz; Mark R. Liles; Ian A. E. Butts; Craig A. Shoemaker; Benjamin H. Beck; Mark Farmer; Timothy J. Bruce (Journal of Fish Diseases, 2024)
Channel catfish ( Ictalurus punctatus ) and Nile tilapia ( Oreochromis niloticus ) are two aquaculture species of great importance. Intensive production is often hindered by poor growth performance and disease mortality. The aim of this study was to evaluate the potential of a commercial fermented yeast product, DVAQUA, on channel catfish and Nile tilapia growth performance metrics and disease resistance. Channel catfish and Nile tilapia were fed practical diets supplemented with 0%, 0.1% or 0.4% of DVAQUA over approximately 2‐month feeding periods in recirculation aquaculture systems. To assess the potential of the postbiotic against common aquaculture pathogens, juvenile catfish were subsequently challenged by immersion with Edwardsiella ictaluri S97‐773 or virulent Aeromonas hydrophila ML09‐119. Nile tilapia juveniles were challenged by injection with Streptococcus iniae ARS‐98‐60. Serum lysozyme activity, blood chemistry and growth metrics were measured at the end of the feeding period, but no differences were observed across the different metrics, except for survival. For the pathogen challenges, there were no differences in endpoint mortality for channel catfish with either pathogen ( p > .05). In contrast, Nile tilapia survivability to S. iniae infection increased proportionally to the inclusion of DVAQUA ( p = .005). Changes to sera lysozyme activity were also noted in the tilapia trial, with a reduction of activity in the fish fed the 0.4% DVAQUA diet compared to the control diet ( p = .031). Expression profiles of proinflammatory genes and antibodies were also found to be modulated in channel catfish fed the postbiotic, indicating some degree of protective response. These results suggest that this postbiotic may be beneficial in protecting Nile tilapia against S. iniae infection by influencing immune parameters and additional research is needed to evaluate the potential of this DVAQUA for improving catfish health and disease control.

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Multivariate mapping of seabed grain size parameters in the Bay of Fundy using convolutional neural networks - Benjamin Misiuk; Yan Liang Tan; Michael Z. Li; Thomas Trappenberg; Ahmadreza Alleosfour; Ian W. Church; Vicki Ferrini; Craig J. Brown (Marine Geology, 2024)

Interplay of management and environmental drivers shifts size structure of reef fish communities - Steven W. J. Canty; A. Justin Nowakowski; Courtney E. Cox; Abel Valdivia; Daniel M. Holstein; Benjamin Limer; Jonathan S. Lefcheck; Nicole Craig; Ian Drysdale; Ana Giro; Mélina Soto; Melanie McField (Global Change Biology, 2024)
Countries are expanding marine protected area (MPA) networks to mitigate fisheries declines and support marine biodiversity. However, MPA impact evaluations typically assess total fish biomass. Here, we examine how fish biomass disaggregated by adult and juvenile life stages responds to environmental drivers, including sea surface temperature (SST) anomalies and human footprint, and multiple management types at 139 reef sites in the Mesoamerican Reef (MAR) region. We found that total fish biomass generally appears stable across the region from 2006 to 2018, with limited rebuilding of fish stocks in MPAs. However, the metric of total fish biomass masked changes in fish community structure, with lower adult than juvenile fish biomass at northern sites, and adult:juvenile ratios closer to 1:1 at southern sites. These shifts were associated with different responses of juvenile and adult fish to environmental drivers and management. Juvenile fish biomass increased at sites with high larval connectivity and coral cover, whereas adult fish biomass decreased at sites with greater human footprint and SST anomalies. Adult fish biomass decreased primarily in Honduran general use zones, which suggests insufficient protection for adult fish in the southern MAR. There was a north–south gradient in management and environmental drivers, with lower coverage of fully protected areas and higher SST anomalies and coastal development in the south that together may undermine the maintenance of adult fish biomass in the southern MAR. Accounting for the interplay between environmental drivers and management in the design of MPAs is critical for increasing fish biomass across life history stages.

Seafloor morphology and substrate mapping in the Gulf of St Lawrence, Canada, using machine learning approaches - Emily Sklar; Esther Bushuev; Benjamin Misiuk; Guillaume Labbé-Morissette; Craig J. Brown (Frontiers in Marine Science, 2024)
Detailed maps of seafloor substrata and morphology can act as valuable proxies for predicting and understanding the distributions of benthic communities and are important for guiding conservation initiatives. High resolution acoustic remote sensing data can facilitate the production of detailed seafloor maps, but are cost-prohibitive to collect and not widely available. In the absence of targeted high resolution data, global bathymetric data of a lower resolution, combined with legacy seafloor sampling data, can provide an alternative for generating maps of seafloor substrate and morphology. Here we apply regression random forest to legacy data in the Gulf of St Lawrence, Canada, to generate a map of seabed sediment distribution. We further apply k-means clustering to a principal component analysis output to identify seafloor morphology classes from the GEBCO bathymetric grid. The morphology classification identified most morphological features but could not discriminate valleys and canyons. The random forest results were in line with previous sediment mapping work done in the area, but a large proportion of zero values skewed the explained variance. In both models, improvements may be possible with the introduction of more predictor variables. These models prove useful for generating regional seafloor maps that may be used for future management and conservation applications.

Size matters: Microherbivores make a big impact in coral aquaculture - Rachel C. Neil; Jonathan A. Barton; Winona Dougan; Symon Dworjanyn; Andrew Heyward; Benjamin Mos; David G. Bourne; Craig Humphrey (Aquaculture, 2024)

Short-interval, high-severity wildfires cause declines in soil seed bank diversity in montane forests of south-eastern Australia - Emily Duivenvoorden; Benjamin Wagner; Craig R. Nitschke; Sabine Kasel (Forest Ecology and Management, 2024)

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Benthic habitat mapping: A review of three decades of mapping biological patterns on the seafloor - Benjamin Misiuk; Craig J. Brown (Estuarine, Coastal and Shelf Science, 2024)

Probiotics enhance resistance to Streptococcus iniae in Nile tilapia ( Oreochromis niloticus ) reared in biofloc systems - Uthpala Padeniya; D. Allen Davis; Mark R. Liles; Stacey A. LaFrentz; Benjamin R. LaFrentz; Craig A. Shoemaker; Benjamin H. Beck; Daniel E. Wells; Timothy J. Bruce (Journal of Fish Diseases, 2023)
Biofloc technology is a rearing technique that maintains desired water quality by manipulating carbon and nitrogen and their inherent mixture of organic matter and microbes. Beneficial microorganisms in biofloc systems produce bioactive metabolites that may deter the growth of pathogenic microbes. As little is known about the interaction of biofloc systems and the addition of probiotics, this study focused on this integration to manipulate the microbial community and its interactions within biofloc systems. The present study evaluated two probiotics ( B. velezensis AP193 and BiOWiSH FeedBuilder Syn 3) for use in Nile tilapia ( Oreochromis niloticus ) culture in a biofloc system. Nine independent 3785 L circular tanks were stocked with 120 juveniles (71.4 ± 4.4 g). Tilapia were fed for 16 weeks and randomly assigned three diets: a commercial control diet or a commercial diet top‐coated with either AP193 or BiOWiSH FeedBuilder Syn3. At 14 weeks, the fish were challenged with a low dose of Streptococcus iniae (ARS‐98‐60, 7.2 × 10 7 CFU mL −1 , via intraperitoneal injection) in a common garden experimental design. At 16 weeks, the fish were challenged with a high dose of S. iniae (6.6 × 10 8 CFU mL −1 ) in the same manner. At the end of each challenge trial, cumulative per cent mortality, lysozyme activity and expression of 4 genes ( il‐1β , il6 , il8 and tnfα ) from the spleen were measured. In both challenges, the mortalities of the probiotic‐fed groups were significantly lower ( p S. iniae . Nonetheless, overall il6 expression was lower in fish challenged with a high dose of ARS‐98‐60, while tnfα expression was lower in fish subjected to a lower pathogen dose. Study findings demonstrate the applicability of probiotics as a dietary supplement for tilapia reared in biofloc systems.

Small-scale oxygen distribution patterns in a coral reef - Adam S. Candy; Shannara K. Taylor Parkins; Fleur C. Van Duyl; Benjamin Mueller; Milou G. I. Arts; Will Barnes; Marie Carstensen; Yun J. H. Scholten; Yusuf C. El-Khaled; Christian Wild; Linda Wegley Kelly; Craig E. Nelson; et al. (Frontiers in Marine Science, 2023)
One mechanism giving fleshy algae a competitive advantage over corals during reef degradation is algal-induced and microbially-mediated hypoxia (typically less than 69.5 µmol oxygen L −1 ). During hypoxic conditions oxygen availability becomes insufficient to sustain aerobic respiration in most metazoans. Algae are more tolerant of low oxygen conditions and may outcompete corals weakened by hypoxia. A key question on the ecological importance of this mechanism remains unanswered: How extensive are local hypoxic zones in highly turbulent aquatic environments, continuously flushed by currents and wave surge? To better understand the concert of biological, chemical, and physical factors that determine the abundance and distribution of oxygen in this environment, we combined 3D imagery, flow measurements, macro- and micro-organismal abundance estimates, and experimentally determined biogenic oxygen and carbon fluxes as input values for a 3D bio-physical model. The model was first developed and verified for controlled flume experiments containing coral and algal colonies in direct interaction. We then developed a three-dimensional numerical model of an existing coral reef plot off the coast of Curaçao where oxygen concentrations for comparison were collected in a small-scale grid using fiberoptic oxygen optodes. Oxygen distribution patterns given by the model were a good predictor for in situ concentrations and indicate widespread localized differences exceeding 50 µmol L -1 over distances less than a decimeter. This suggests that small-scale hypoxic zones can persist for an extended period of time in the turbulent environment of a wave- and surge- exposed coral reef. This work highlights how the combination of three-dimensional imagery, biogenic fluxes, and fluid dynamic modeling can provide a powerful tool to illustrate and predict the distribution of analytes (e.g., oxygen or other bioactive substances) in a highly complex system.

The loss of cardiac SIRT3 decreases metabolic flexibility and proteostasis in an age-dependent manner - Ping Li; Maria F. Newhardt; Satoshi Matsuzaki; Craig Eyster; Atul Pranay; Frederick F. Peelor; Albert Batushansky; Caroline Kinter; Kumar Subramani; Sandeep Subrahmanian; Jasimuddin Ahamed; Pengchun Yu; et al. (GeroScience, 2023)
SIRT3 is a longevity factor that acts as the primary deacetylase in mitochondria. Although ubiquitously expressed, previous global SIRT3 knockout studies have shown primarily a cardiac-specific phenotype. Here, we sought to determine how specifically knocking out SIRT3 in cardiomyocytes (SIRTcKO mice) temporally affects cardiac function and metabolism. Mice displayed an age-dependent increase in cardiac pathology, with 10-month-old mice exhibiting significant loss of systolic function, hypertrophy, and fibrosis. While mitochondrial function was maintained at 10 months, proteomics and metabolic phenotyping indicated SIRT3 hearts had increased reliance on glucose as an energy substrate. Additionally, there was a significant increase in branched-chain amino acids in SIRT3cKO hearts without concurrent increases in mTOR activity. Heavy water labeling experiments demonstrated that, by 3 months of age, there was an increase in protein synthesis that promoted hypertrophic growth with a potential loss of proteostasis in SIRT3cKO hearts. Cumulatively, these data show that the cardiomyocyte-specific loss of SIRT3 results in severe pathology with an accelerated aging phenotype.

Transcriptome analysis of Pacific white shrimp (Liptopenaeus vannamei) after exposure to recombinant Vibrio parahaemolyticus PirA and PirB proteins - Miles D. Lange; Jason Abernathy; Anna A. Rawles; Dunhua Zhang; Craig A. Shoemaker; Troy J. Bader; Benjamin H. Beck (Fish & Shellfish Immunology, 2023)

Abrasive wear in heat-treated ostrich eggshell beads: implications for the archaeological record - Caitlin Craig; Benjamin Collins; April Nowell; Christopher J. H. Ames (Archaeological and Anthropological Sciences, 2023)

Evaluation of basal melting parameterisations using in situ ocean and melting observations from the Amery Ice Shelf, East Antarctica - Madelaine Rosevear; Benjamin Galton-Fenzi; Craig Stevens (Ocean Science, 2022)
Ocean-driven melting of Antarctic ice shelves is causing accelerating loss of grounded ice from the Antarctic continent. However, the ocean processes governing ice shelf melting are not well understood, contributing to uncertainty in projections of Antarctica's contribution to sea level. Here, we analyse oceanographic data and in situ measurements of ice shelf melt collected from an instrumented mooring beneath the centre of the Amery Ice Shelf, East Antarctica. This is the first direct measurement of basal melting from the Amery Ice Shelf and was made through the novel application of an upward-facing acoustic Doppler current profiler (ADCP). ADCP data were also used to map a region of the ice base, revealing a steep topographic feature or “scarp” in the ice with vertical and horizontal scales of ∼ 20 and ∼ 40 m, respectively. The annually averaged ADCP-derived melt rate of 0.51 ± 0.18 m yr−1 is consistent with previous modelling results and glaciological estimates. There is significant seasonal variation around the mean melt rate, with a 40 % increase in melting in May and a 60 % decrease in September. Melting is driven by temperatures ∼ 0.2 ∘C above the local freezing point and background and tidal currents, which have typical speeds of 3.0 and 10.0 cm s−1, respectively. We use the coincident measurements of ice shelf melt and oceanographic forcing to evaluate parameterisations of ice–ocean interactions and find that parameterisations in which there is an explicit dependence of the melt rate on current speed beneath the ice tend to overestimate the local melt rate at AM06 by between 200 % and 400 %, depending on the choice of drag coefficient. A convective parameterisation in which melting is a function of the slope of the ice base is also evaluated and is shown to underpredict melting by 20 % at this site. By combining these new estimates with available observations from other ice shelves, we show that the commonly used current speed-dependent parameterisation overestimates melting at all but the coldest and most energetic cavity conditions.

Benefits and Challenges of a Stakeholder-Driven Shellfish Toxicity Forecast in Coastal Maine - Nicholas R. Record; Johnathan Evanilla; Kohl Kanwit; Craig Burnell; Carmen Cartisano; Bryant J. Lewis; Jill MacLeod; Benjamin Tupper; David W. Miller; Adrienne T. Tracy; Carol White; Matt Moretti; et al. (Frontiers in Marine Science, 2022)
Paralytic shellfish poison (PSP) is a human health concern for shellfish aquaculture and wild harvest. This paper discusses lessons learned from a forecasting program for PSP in coastal Maine, USA, designed based on stakeholder input, and run in an operational mode for the 2021 season. The forecast uses a deep learning algorithm to make site-specific, probabilistic forecasts at a weekly forecast range for toxin levels measured in shellfish tissue. Forecasts had high accuracy in the 2021 season, correctly predicting closure events and locations despite a highly unusual season. Stakeholders reported a positive view of the forecast system, and stakeholder input continues to be of key importance as further modifications are made to the system. There are benefits and challenges to the stakeholder-based design of the system.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Extreme longevity variants at the FOXO3 locus may moderate FOXO3 isoform levels - Ryan Frankum; Tom S. O. Jameson; Bridget A. Knight; Francis B. Stephens; Benjamin T. Wall; Timothy A. Donlon; Trevor Torigoe; Bradley J. Willcox; D. Craig Willcox; Richard C. Allsopp; Lorna W. Harries (GeroScience, 2022)

Extreme longevity variants at the FOXO3 locus may moderate FOXO3 isoform levels - Ryan Frankum; Tom S. O. Jameson; Bridget A. Knight; Francis B. Stephens; Benjamin T. Wall; Timothy A. Donlon; Trevor Torigoe; Bradley J. Willcox; D. Craig Willcox; Richard C. Allsopp; Lorna W. Harries (GeroScience, 2022)
The rs2802292, rs2764264 and rs13217795 variants of FOXO3 have been associated with extreme longevity in multiple human populations, but the mechanisms underpinning this remain unclear. We aimed to characterise potential effects of longevity-associated variation on the expression and mRNA processing of the FOXO3 gene. We performed a comprehensive assessment of FOXO3 isoform usage across a wide variety of human tissues and carried out a bioinformatic analysis of the potential for longevity-associated variants to disrupt regulatory regions involved in isoform choice. We then related the expression of full length and 5′ truncated FOXO3 isoforms to rs13217795 genotype in peripheral blood and skeletal muscle from individuals of different rs13217795 genotypes. FOXO3 isoforms displayed considerable tissue specificity. We determined that rs13231195 and its tightly aligned proxy variant rs9400239 may lie in regulatory regions involved in isoform choice. The longevity allele at rs13217795 was associated with increased levels of full length FOXO3 isoforms in peripheral blood and a decrease in truncated FOXO3 isoforms in skeletal muscle RNA. We suggest that the longevity effect of FOXO3 SNPs may in part derive from a shift in isoform usage in skeletal muscle away from the production of 5′ truncated FOXO3 isoforms lacking a complete forkhead DNA binding domain, which may have compromised functionality.

Multiple imputation of multibeam angular response data for high resolution full coverage seabed mapping - Benjamin Misiuk; Craig J. Brown (Marine Geophysical Research, 2022)
Acoustic data collected by multibeam echosounders (MBES) are increasingly used for high resolution seabed mapping. The relationships between substrate properties and the acoustic response of the seafloor depends on the acoustic angle of incidence and the operating frequency of the sonar, and these dependencies can be analysed for discrimination of benthic substrates or habitats. An outstanding challenge for angular MBES mapping at a high spatial resolution is discontinuity; acoustic data are seldom represented at a full range of incidence angles across an entire survey area, hindering continuous spatial mapping. Given quantifiable relationships between MBES data at various incidence angles and frequencies, we propose to use multiple imputation to achieve complete estimates of angular MBES data over full survey extents at a high spatial resolution for seabed mapping. The primary goals of this study are (i) to evaluate the effectiveness of multiple imputation for producing accurate estimates of angular backscatter intensity and substrate penetration information, and (ii) to evaluate the usefulness of imputed angular data for benthic habitat and substrate mapping at a high spatial resolution. Using a multi-frequency case study, acoustic soundings were first aggregated to homogenous seabed units at a high spatial resolution via image segmentation. The effectiveness and limitations of imputation were explored in this context by simulating various amounts of missing angular data, and results suggested that a substantial proportion of missing measurements (> 40%) could be imputed with little error using Multiple Imputation by Chained Equations (MICE). The usefulness of imputed angular data for seabed mapping was then evaluated empirically by using MICE to generate multiple stochastic versions of a dataset with missing angular measurements. The complete, imputed datasets were used to model the distribution of substrate properties observed from ground-truth samples using Random Forest and neural networks. Model results were pooled for continuous spatial prediction and estimates of confidence were derived to reflect uncertainty resulting from multiple imputations. In addition to enabling continuous spatial prediction, the high-resolution imputed angular models performed favourably compared to broader segmentations or non-angular data.

Synergism between feremycorrhizal symbiosis and free-living diazotrophs leads to improved growth and nutrition of wheat under nitrogen deficiency conditions - Khalil Kariman; Benjamin Moreira-Grez; Craig Scanlan; Saleh Rahimlou; Gustavo Boitt; Zed Rengel (Biology and Fertility of Soils, 2022)
A controlled-environment study was conducted to explore possible synergistic interactions between the feremycorrhizal (FM) fungus Austroboletus occidentalis and soil free-living N 2 -fixing bacteria (diazotrophs). Wheat ( Triticum aestivum ) plants were grown under N deficiency conditions in a field soil without adding microbial inoculum (control: only containing soil indigenous microbes), or inoculated with a consortium containing four free-living diazotroph isolates (diazotrophs treatment), A. occidentalis inoculum (FM treatment), or both diazotrophs and A. occidentalis inoculums (dual treatment). After 7 weeks of growth, significantly greater shoot biomass was observed in plants inoculated with diazotrophs (by 25%), A. occidentalis (by 101%), and combined inoculums (by 106%), compared to the non-inoculated control treatment. All inoculated plants also had higher shoot nutrient contents (including N, P, K, Mg, Zn, Cu, and Mn) than the control treatment. Compared to the control and diazotrophs treatments, significantly greater shoot N content was observed in the FM treatment (i.e., synergism between the FM fungus and soil indigenous diazotrophs). Dually inoculated plants had the highest content of nutrients in shoots (e.g., N, P, K, S, Mg, Zn, Cu, and Mn) and soil total N (13–24% higher than the other treatments), i.e., synergism between the FM fungus and added diazotrophs. Root colonization by soil indigenous arbuscular mycorrhizal fungi declined in all inoculated plants compared to control. Non-metric multidimensional scaling (NMDS) analysis of the bacterial 16S rRNA gene amplicons revealed that the FM fungus modified the soil microbiome. Our in vitro study indicated that A. occidentalis could not grow on substrates containing lignocellulosic materials or sucrose, but grew on media supplemented with hexoses such as glucose and fructose, indicating that the FM fungus has limited saprotrophic capacity similar to ectomycorrhizal fungi. The results revealed synergistic interactions between A. occidentalis and soil free-living diazotrophs, indicating a potential to boost microbial N 2 fixation for non-legume crops.

Identification and Characterization of Differentially Expressed IgM Transcripts of Channel Catfish Vaccinated with Antigens of Virulent Aeromonas hydrophila - Dunhua Zhang; Miles D. Lange; Craig A. Shoemaker; Benjamin H. Beck (Fishes, 2022)
Channel catfish (Ictalurus punctatus) is the top species produced in US aquaculture and motile Aeromonas septicemia, caused by virulent Aeromonas hydrophila (vAh), is one of the most severe diseases that afflict catfish farms. Previously, vaccination of fish with extracellular proteins (ECP) of vAh was shown to produce a robust antibody-mediated immune response against vAh infection. In this study, we analyzed IgM transcripts that were differentially expressed in the head kidney and liver of ECP-immunized and mock-immunized (control) fish with emphasis on a variable domain of heavy chain. Quantitative PCR analysis indicated that immunized fish produced significantly more IgM transcripts than control fish. Full-length IgM heavy chain cDNA was cloned, which encoded typical IgM peptide, including signal peptide, variable domain (VH), constant domain (CH), and carboxyl terminal peptide. Great sequence diversity was revealed in a VH segment, with the third complementarity diversity region (CDR3) being most variable. Using germline VH gene grouping method, variants (clones) of VH characterized in this study belonged to nine VH families. The most unique variants (approximately 49%) were found in the VH2 family. Vaccinated fish apparently had more unique variants than in the control fish. There were 62% and 79% of unique variants in the head kidney and liver of vaccinated fish, respectively, while 44% and 27% unique variants in the head kidney and liver of control fish, respectively. Among the unique variants in VH2 family, approximately 87% of them were found in vaccinated fish. Two-dimensional gel electrophoresis of semi-purified IgM protein confirmed that matured IgM protein was as variable as IgM transcripts identified in this study, with isoelectric points crossing from 6 to 10. Results of this study provided insight into the molecular and genetic basis of antibody diversity and enriched our knowledge of the complex interplay between antigens and antibodies in Ictalurid catfish.

Biological mechanisms may contribute to soil carbon saturation patterns - Matthew E. Craig; Melanie A. Mayes; Benjamin N. Sulman; Anthony P. Walker (Global Change Biology, 2021)
Increasing soil organic carbon (SOC) storage is a key strategy to mitigate rising atmospheric CO 2 , yet SOC pools often appear to saturate, or increase at a declining rate, as carbon (C) inputs increase. Soil C saturation is commonly hypothesized to result from the finite amount of reactive mineral surface area available for retaining SOC, and is accordingly represented in SOC models as a physicochemically determined SOC upper limit. However, mineral‐associated SOC is largely microbially generated. In this perspective, we present the hypothesis that apparent SOC saturation patterns could emerge as a result of ecological constraints on microbial biomass—for example, via competition or predation—leading to reduced C flow through microbes and a reduced rate of mineral‐associated SOC formation as soil C inputs increase. Microbially explicit SOC models offer an opportunity to explore this hypothesis, yet most of these models predict linear microbial biomass increases with C inputs and insensitivity of SOC to input rates. Synthesis of 54 C addition studies revealed constraints on microbial biomass as C inputs increase. Different hypotheses limiting microbial density were embedded in a three‐pool SOC model without explicit limits on mineral surface area. As inputs increased, the model demonstrated either no change, linear, or apparently saturating increases in mineral‐associated and particulate SOC pools. Taken together, our results suggest that microbial constraints are common and could lead to reduced mineral‐associated SOC formation as input rates increase. We conclude that SOC responses to altered C inputs—or any environmental change—are influenced by the ecological factors that limit microbial populations, allowing for a wider range of potential SOC responses to stimuli. Understanding how biotic versus abiotic factors contribute to these patterns will better enable us to predict and manage soil C dynamics.

Occupant Restraint in Far-Side Impacts: Cadaveric and WorldSID Responses to a Far-Side Airbag - Daniel Perez-Rapela; John-Paul Donlon; Jason L. Forman; Bengt Pipkorn; Benjamin K. Shurtz; Craig Markusic; Jeff R. Crandall (Annals of Biomedical Engineering, 2021)

A new maximum size for the family Nomeidae and the third record of a longfin cigarfish, Cubiceps paradoxus (Stromateoidei: Nomeidae) from California, USA - Benjamin W. Frable; Merit H. Mccrea; Milton S. Love; Matthew T. Craig (Journal of Fish Biology, 2020)
We report the largest specimen from the stromateoid family Nomeidae. The specimen, measuring 1283 mm total length unpreserved, was caught on hook and line from shore in Port Hueneme, California, USA in June 2019. Despite scavenging damage, the specimen was identified as a longfin cigarfish, Cubiceps paradoxus, using morphological characters and molecular techniques. This is the third record of C. paradoxus from California. We also provide an account of a previously unreported C. paradoxus collected off the US‐Mexico Border in 1999 that was examined but not preserved.

Pericytes, inflammation, and diabetic retinopathy - Benjamin G. Spencer; Jose J. Estevez; Ebony Liu; Jamie E. Craig; John W. Finnie (Inflammopharmacology, 2020)

Mapping Exposure to Flooding in Three Coastal Communities on the North Slope of Alaska Using Airborne LiDAR - Trevor C. Lantz; Nina D. Moffat; Benjamin M. Jones; Qi Chen; Craig E. Tweedie (Coastal Management, 2020)

A Framework for the Development, Design and Implementation of a Sustained Arctic Ocean Observing System - Craig M. Lee; Sandy Starkweather; Hajo Eicken; Mary-Louise Timmermans; Jeremy Wilkinson; Stein Sandven; Dmitry Dukhovskoy; Sebastian Gerland; Jacqueline Grebmeier; Janet M. Intrieri; Sung-Ho Kang; Molly McCammon; et al. (Frontiers in Marine Science, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Cognitive demand of eccentric versus concentric cycling and its effects on post-exercise attention and vigilance - Benjamin Kan; Craig Speelman; Kazunori Nosaka (European Journal of Applied Physiology, 2019)

Developing an Integrated Ocean Observing System for New Zealand - Joanne O’Callaghan; Craig Stevens; Moninya Roughan; Chris Cornelisen; Philip Sutton; Sally Garrett; Giacomo Giorli; Robert O. Smith; Kim I. Currie; Sutara H. Suanda; Michael Williams; Melissa Bowen; et al. (Frontiers in Marine Science, 2019)

Antimicrobial activity of the biopolymer chitosan against Streptococcus iniae - Benjamin H. Beck; Mediha Yildirim‐Aksoy; Craig A. Shoemaker; Sidney Adam Fuller; Eric Peatman (Journal of Fish Diseases, 2019)
The antimicrobial activity and mode of action of chitosan were evaluated against Streptococcus iniae , a pathogenic Gram‐positive bacterium of fish worldwide. Cell proliferation kinetics were examined following exposure to varying concentrations of chitosan. The action of chitosan on S. iniae was also investigated by measuring agglutination activity, conductivity, and extracellular and intracellular bacterial adenosine triphosphate (ATP) levels. Chitosan exhibited antibacterial activity against S. iniae at concentrations of 0.1% and above and was lethal at a concentration of 0.4% and higher. The mechanism of antibacterial activity of chitosan at the inhibitory level of bacterial growth appears to hinge upon the interaction between chitosan and the oppositely charged bacterial surface. This interplay causes agglutination, which was readily observed grossly and microscopically. After interacting with the cell surface via adsorption, an efflux of intracellular ATP was documented, which suggests that chitosan disrupts the bacterial cell causing leakage of cytosolic contents and ultimately cell death. Results suggest chitosan may be worth evaluating as a natural alternative to antibiotic against S. iniae infection of fish.

Influence of native catfish mucus on Flavobacterium columnare growth and proteolytic activity - Craig A. Shoemaker; Benjamin R. LaFrentz; Eric Peatman; Benjamin H. Beck (Journal of Fish Diseases, 2018)
Flavobacterium columnare causes columnaris disease of farmed and wild freshwater fish. Skin mucus is an important factor in early stages of columnaris pathogenesis, albeit little studied. Our objectives were to (a) characterize the terminal glycosylation pattern ( TGP ) of catfish mucus, (b) determine the growth of F. columnare in formulated water ( FW )‐containing channel catfish ( Ictalurus punctatus ) or hybrid catfish ( Ictalurus punctatus X Ictalurus furcatus ) mucus and (c) examine extracellular protease activity of two F. columnare isolates differing in virulence. The TGP of catfish mucus by lectin binding was as follows: alpha‐D‐mannose/alpha‐D‐glucose >N‐acetyl‐beta‐D‐glucosamine >N‐acetyl‐beta‐D‐glucosamine/N‐acetylneuraminic acid >N‐acetyl‐D‐galactosamine >alpha‐D‐galactose/N‐acetyl‐alpha‐D‐galactosamine >beta‐D‐galactose = alpha‐L‐fucose. Virulence studies demonstrated isolate AL ‐02‐36 was highly virulent in channel catfish fry (0.1 g) with cumulative mortality of 90%‐100% versus 60% for isolate ALG ‐00‐530 at equivalent doses (~3 × 10 6 CFU / ml ); a similar result was observed in larger (0.7 g) catfish. In multiple experiments, F. columnare replicated (2‐3 logs) and survived (28 days) in formulated water‐containing catfish mucus. Highly virulent isolate AL ‐02‐36 possessed at least 2.5‐ to fivefold higher protease activity following growth in mucus than the less virulent ALG ‐00‐530. Flavobacterium columnare utilized catfish mucus as a nutrient source and mucus presence modulated extracellular protease production.

Tree mycorrhizal type predicts within‐site variability in the storage and distribution of soil organic matter - Matthew E. Craig; Benjamin L. Turner; Chao Liang; Keith Clay; Daniel J. Johnson; Richard P. Phillips (Global Change Biology, 2018)
Forest soils store large amounts of carbon (C) and nitrogen (N), yet how predicted shifts in forest composition will impact long‐term C and N persistence remains poorly understood. A recent hypothesis predicts that soils under trees associated with arbuscular mycorrhizas ( AM ) store less C than soils dominated by trees associated with ectomycorrhizas ( ECM ), due to slower decomposition in ECM ‐dominated forests. However, an incipient hypothesis predicts that systems with rapid decomposition—e.g. most AM ‐dominated forests—enhance soil organic matter ( SOM ) stabilization by accelerating the production of microbial residues. To address these contrasting predictions, we quantified soil C and N to 1 m depth across gradients of ECM ‐dominance in three temperate forests. By focusing on sites where AM ‐ and ECM ‐plants co‐occur, our analysis controls for climatic factors that covary with mycorrhizal dominance across broad scales. We found that while ECM stands contain more SOM in topsoil, AM stands contain more SOM when subsoil to 1 m depth is included. Biomarkers and soil fractionations reveal that these patterns are driven by an accumulation of microbial residues in AM ‐dominated soils. Collectively, our results support emerging theory on SOM formation, demonstrate the importance of subsurface soils in mediating plant effects on soil C and N, and indicate that shifts in the mycorrhizal composition of temperate forests may alter the stabilization of SOM .

Distinct Siderophores Contribute to Iron Cycling in the Mesopelagic at Station ALOHA - Randelle M. Bundy; Rene M. Boiteau; Craig McLean; Kendra A. Turk-Kubo; Matt R. McIlvin; Mak A. Saito; Benjamin A. S. Van Mooy; Daniel J. Repeta (Frontiers in Marine Science, 2018)

Autonomous Multi-Platform Observations During the Salinity Processes in the Upper-ocean Regional Study - Eric Lindstrom; Andrey Shcherbina; Luc Rainville; Thomas Farrar; Luca Centurioni; Shenfu Dong; Eric D’Asaro; Charles Eriksen; David Fratantoni; Benjamin Hodges; Verena Hormann; William Kessler; et al. (Oceanography, 2017)

Litter decay controlled by temperature, not soil properties, affecting future soil carbon - Edward G. Gregorich; Henry Janzen; Benjamin H. Ellert; Bobbi L. Helgason; Budong Qian; Bernie J. Zebarth; Denis A. Angers; Ronald P. Beyaert; Craig F. Drury; Scott D. Duguid; William E. May; Brian G. McConkey; et al. (Global Change Biology, 2017)
Widespread global changes, including rising atmospheric CO 2 concentrations, climate warming and loss of biodiversity, are predicted for this century; all of these will affect terrestrial ecosystem processes like plant litter decomposition. Conversely, increased plant litter decomposition can have potential carbon‐cycle feedbacks on atmospheric CO 2 levels, climate warming and biodiversity. But predicting litter decomposition is difficult because of many interacting factors related to the chemical, physical and biological properties of soil, as well as to climate and agricultural management practices. We applied 13 C‐labelled plant litter to soil at ten sites spanning a 3500‐km transect across the agricultural regions of Canada and measured its decomposition over five years. Despite large differences in soil type and climatic conditions, we found that the kinetics of litter decomposition were similar once the effect of temperature had been removed, indicating no measurable effect of soil properties. A two‐pool exponential decay model expressing undecomposed carbon simply as a function of thermal time accurately described kinetics of decomposition. ( R 2 = 0.94; RMSE = 0.0508). Soil properties such as texture, cation exchange capacity, pH and moisture, although very different among sites, had minimal discernible influence on decomposition kinetics. Using this kinetic model under different climate change scenarios, we projected that the time required to decompose 50% of the litter (i.e. the labile fractions) would be reduced by 1–4 months, whereas time required to decompose 90% of the litter (including recalcitrant fractions) would be reduced by 1 year in cooler sites to as much as 2 years in warmer sites. These findings confirm quantitatively the sensitivity of litter decomposition to temperature increases and demonstrate how climate change may constrain future soil carbon storage, an effect apparently not influenced by soil properties.

Phylogenomics at the tips: inferring lineages and their demographic history in a tropical lizard, Carlia amax - Sally Potter; Jason G. Bragg; Benjamin M. Peter; Ke Bi; Craig Moritz (Molecular Ecology, 2016)
High‐throughput sequencing approaches offer opportunities to better understand the evolutionary processes driving diversification, particularly in nonmodel organisms. In particular, the 100–1000's of loci that can now be sequenced are providing unprecedented power in population, speciation and phylogenetic studies. Here, we apply an exon capture approach to generate >99% complete sequence and SNP data across >2000 loci from a tropical skink, Carlia amax , and exploit these data to identify divergent lineages and infer their relationships and demographic histories. This is especially relevant to low‐dispersal tropical taxa that often have cryptic diversity and spatially dynamic histories. For C. amax , clustering of nuclear SNP s and coalescent‐based species delimitation analyses identify four divergent lineages, one fewer than predicted based on geographically coherent mt DNA clades (>9.4% sequence divergence). Three of these lineages are widespread and parapatric on the mainland, whereas the most divergent is restricted to islands off the northeast Northern Territory. Tests for population expansion reject an equilibrium isolation‐by‐distance model for two of the three widespread lineages and infer refugial expansion sources in the relatively mesic northeast Top End and northwest Kimberley. The latter is already recognized as a hotspot of endemism, but our results also suggest that a stronger focus on the northeast Top End, and adjacent islands is warranted. More generally, our results show how genome‐reduction methods such as exon capture can yield insights into the pattern and dynamics of biodiversity across complex landscapes with as yet poorly understood biogeographic history and how exon data can link between population and phylogenetic questions.

Combining ability and heterosis for yield and drought tolerance traits under managed drought stress in sweetpotato - Kivuva Benjamin Musembi; Stephen Mwangi Githiri; George Craig Yencho; Julia Sibiya (Euphytica, 2015)

Understanding the Role of the Biological Pump in the Global Carbon Cycle: An Imperative for Ocean Science - Susumu Honjo; Timothy Eglinton; Craig Taylor; Kevin Ulmer; Stefan Sievert; Astrid Bracher; Christopher German; Virginia Edgcomb; Roger Francois; M. Debora Iglesias-Rodriguez; Benjamin Van Mooy; Daniel Rapeta (Oceanography, 2014)

Influence of exercise intensity on respiratory muscle fatigue and brachial artery blood flow during cycling exercise - Joshua R. Smith; Carl J. Ade; Ryan M. Broxterman; Benjamin C. Skutnik; Thomas J. Barstow; Brett J. Wong; Craig A. Harms (European Journal of Applied Physiology, 2014)

Evaluations of combined zebrafish (Danio rerio) embryo and marine phytoplankton (Diacronema lutheri) toxicity of dissolved organic contaminants in the Ythan catchment, Scotland, UK - Emmanuel S. Emelogu; Thomas-Benjamin Seiler; Pat Pollard; Craig D. Robinson; Lynda Webster; Craig McKenzie; Sebastian Heger; Henner Hollert; Eileen Bresnan; Jennifer Best; Colin F. Moffat (Environmental Science and Pollution Research, 2014)

Prostate Tissue Metal Levels and Prostate Cancer Recurrence in Smokers - Christine Neslund-Dudas; Ashoka Kandegedara; Oleksandr N. Kryvenko; Nilesh Gupta; Craig Rogers; Benjamin A. Rybicki; Q. Ping Dou; Bharati Mitra (Biological Trace Element Research, 2014)

Variation in hair δ13C and δ15N values in long-tailed macaques (Macaca fascicularis) from Singapore - Michael A. Schillaci; J. Margaret Castellini; Craig A. Stricker; Lisa Jones-Engel; Benjamin P. Y.-H. Lee; Todd M. O’Hara (Primates, 2014)

Hypermorphic expression of centromeric retroelement-encoded small RNAs impairs CENP-A loading - Dawn M. Carone; Chu Zhang; Laura E. Hall; Craig Obergfell; Benjamin R. Carone; Michael J. O’Neill; Rachel J. O’Neill (Chromosome Research, 2013)

Groundwater recharge to a sedimentary aquifer in the topographically closed Uley South Basin, South Australia - Carlos M. Ordens; Adrian D. Werner; Vincent E. A. Post; John L. Hutson; Craig T. Simmons; Benjamin M. Irvine (Hydrogeology Journal, 2012)

Adapting to climate change through local municipal planning: barriers and challenges - Thomas G. Measham; Benjamin L. Preston; Timothy F. Smith; Cassandra Brooke; Russell Gorddard; Geoff Withycombe; Craig Morrison (Mitigation and Adaptation Strategies for Global Change, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Targeting the Ubiquitin E3 Ligase MuRF1 to Inhibit Muscle Atrophy - Michael J. Eddins; Jeffrey G. Marblestone; K. G. Suresh Kumar; Craig A. Leach; David E. Sterner; Michael R. Mattern; Benjamin Nicholson (Cell Biochemistry and Biophysics, 2011)

Prevalence of Cancer Visits by Physician Specialty, 1997–2006 - Benjamin M. Craig; Bethany A. Bell; Gwendolyn P. Quinn; Susan T. Vadaparampil (Journal of Cancer Education, 2010)

Conserved and Variant Molecular and Functional Features of Multiple Egg Yolk Precursor Proteins (Vitellogenins) in White Perch (Morone americana) and other Teleosts - Benjamin J. Reading; Naoshi Hiramatsu; Sayumi Sawaguchi; Takahiro Matsubara; Akihiko Hara; Mark O. Lively; Craig V. Sullivan (Marine Biotechnology, 2009)

Radiation hybrid map of the porcine genome comprising 2035 EST loci - Anette Rink; Katie Eyer; Benjamin Roelofs; Kimberly J. Priest; Kathleen J. Sharkey-Brockmeier; Sudkamon Lekhong; Elif K. Karajusuf; Jason Bang; Martine Yerle; Denis Milan; Wan-Sheng Liu; Craig W. Beattie (Mammalian Genome, 2006)

Size correction: comparing morphological traits among populations and environments - Michael W. McCoy; Benjamin M. Bolker; Craig W. Osenberg; Benjamin G. Miner; James R. Vonesh (Oecologia, 2006)

Intraspecific Variation in Odor-Mediated Host Preference of the Mosquito Culex annulirostris - Craig R. Williams; Michael J. Kokkinn; Benjamin P. Smith (Journal of Chemical Ecology, 2003)

A first-generation EST RH comparative map of the porcine and human genome - Anette Rink; Elizabeth M. Santschi; Katie M. Eyer; Benjamin Roelofs; Markus Hess; Myra Godfrey; Elif K. Karajusuf; Martine Yerle; Denis Milan; Craig W. Beattie (Mammalian Genome, 2002)